2012
DOI: 10.1038/eye.2012.247
|View full text |Cite
|
Sign up to set email alerts
|

Molecular pathology of lymphoma

Abstract: Ocular lymphomas can be divided into intraocular lymphomas and ocular adnexal lymphomas. The vitreoretinal lymphomausually a diffuse large B-cell lymphoma (DLBCL) of high-grade malignancy-is the most common lymphoid malignancy arising in the eye, while the extranodal marginal zone B-cell lymphoma (EMZL), an indolent often recurrent tumour, occurs most frequently in the ocular adnexal tissue. The two lymphoma subtypes differ significantly in their clinical presentation, subsequent course and outcome as well as … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
28
0
4

Year Published

2013
2013
2020
2020

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 52 publications
(34 citation statements)
references
References 79 publications
(97 reference statements)
2
28
0
4
Order By: Relevance
“…20,30,91 Another 15%e20% of ocular adnexal EMZL patients carry the t(3;14)(p14;q32) translocation, whereas t(1;14)(p22;q32) occurs in approximately 10% of these. 20,30,123 Additionally, t(5;14)(q34;q32) and t(9;14)(p24;q32) translocations have been recognized as potentially taking part in the development of ocular adnexal EMZL and their roles need further investigation, which also regards the newly detected (5;11)(q33;p11.2) translocation in a case of conjunctival EMZL. 28,30 Trisomy of chromosomes 3 and 18 is another cytogenetic abnormality associated with EMZL.…”
Section: Extranodal Marginal Zone Lymphomamentioning
confidence: 97%
See 2 more Smart Citations
“…20,30,91 Another 15%e20% of ocular adnexal EMZL patients carry the t(3;14)(p14;q32) translocation, whereas t(1;14)(p22;q32) occurs in approximately 10% of these. 20,30,123 Additionally, t(5;14)(q34;q32) and t(9;14)(p24;q32) translocations have been recognized as potentially taking part in the development of ocular adnexal EMZL and their roles need further investigation, which also regards the newly detected (5;11)(q33;p11.2) translocation in a case of conjunctival EMZL. 28,30 Trisomy of chromosomes 3 and 18 is another cytogenetic abnormality associated with EMZL.…”
Section: Extranodal Marginal Zone Lymphomamentioning
confidence: 97%
“…20,30,123 Additionally, t(5;14)(q34;q32) and t(9;14)(p24;q32) translocations have been recognized as potentially taking part in the development of ocular adnexal EMZL and their roles need further investigation, which also regards the newly detected (5;11)(q33;p11.2) translocation in a case of conjunctival EMZL. 28,30 Trisomy of chromosomes 3 and 18 is another cytogenetic abnormality associated with EMZL. 86,109,134 Gains of chromosome 3 are rarely found in EMZL of the conjunctiva, whereas trisomy 18 is very common in conjunctival EMZL, found in as many as 67% of patients.…”
Section: Extranodal Marginal Zone Lymphomamentioning
confidence: 97%
See 1 more Smart Citation
“…As we known, IκB is a specific inhibitor of the NFκB transcription factor (Baeuerle et al, 1988). It has become clear that aberrant deregulated NFκB activation is a hallmark of several lymphoid malignancies, particularly MALT lymphoma (Coupland et al, 2013). Moreover, it has been reported that VCP can inhibit apoptosis and facilitate metastasis of the Osteosarcoma Cell Line (Asai et al, 2002).…”
Section: Introductionmentioning
confidence: 99%
“…Der Begriff primäres vitreoretinales Lymphom (PVRL) sollte für Lymphome verwendet werden, die den Glaskörper (GK), N. opticus und das retinale Pigmentepithel (RPE) beteiligen und häufig mit einem primären ZNS-Lymphom assoziiert sind [1]. Das PVRL ist meist ein diffuses großzelliges B-Zell-Lymphom von hoher Malignität [2] und meist bilateral. Jedoch können ebenfalls T-Zell-Lymphome vorkommen [3].…”
unclassified